(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The importance of herbals in neurodegenerative disorders lies in their ability to offer multifaceted therapeutic benefits, including neuroprotection, anti-inflammation, antioxidant effects and cognitive enhancement. Karnasphota is a memory enhancer as per Ayurveda and is described as Medhya. This claim is evaluated scientifically for the scope of treating neurodegenerative disorders. Proximate analysis and phytochemical profiling were performed after solvent extraction of the powdered root of C. halicacabum L. An in vitro DPPH antioxidant assay, acetylcholinesterase and tyrosinase enzyme inhibition effect was carried out to identify the capability of root extract as a neuro-shielding agent. The total content of bioactive triterpenoid lupeol was estimated by HPTLC followed by its isolation. The total lupeol content as a bioactive marker found was 6.400 µg. The plant root phytoconstituents are potent antioxidants with IC50 89.08 µg, comparable to the positive control. The potency of the phytoconstituents was demonstrated by in vitro inhibition of acetylcholinesterase and tyrosinase enzymes as compared to Physostigmine and Pregabalin respectively by HPLC that shows optimum potency compared to standards. An in-silico study against AChE evaluated the potential of the identified phytoconstituents. An in-silico study revealed most phytoconstituents are promising anti-Alzheimer's leads compared to Donepezil, an acetylcholinesterase inhibitor.